The relationship between language anxiety and the actual and perceived levels of foreign language pronunciation - Baran-Łucarz, Małgorzata (Studies in Second Language Learning and Teaching, 2011)
The construct of anxiety has been captivating the interest of SLA researchers for a long time. Numerous observations show that most individuals experience anxiety when learning a foreign language (FL) and using it, both in classroom and real-life contexts, though to a different extent. An analysis of studies conducted on language anxiety (LA) throughout several decades (Horwitz, 2010) shows that researchers have focused, first and foremost, on examining the nature, symptoms and consequences of being anxious, proving its detrimental effect on FL and L2 learning and performance. However, the causes of LA seem to have been less thoroughly explored. The paper reports on a study investigating whether the actual level of FL learners’ pronunciation and the pronunciation level perceived by students can be considered significant sources of anxiety. It is hypothesized that both pronunciation levels are related to LA, with the latter being a more important determinant of LA than the former. To measure the subjects’ degree of anxiety, the Foreign Language Classroom Anxiety Scale (Horwitz, Horwitz, & Cope, 1986) was applied. The actual level of pronunciation was diagnosed with the use of a Pronunciation Test, consisting of a Perception Test and two Production Tests (word and passage reading). The perceived pronunciation level of the participants was measured with a questionnaire designed for the purpose of this research. The Pearson moment-correlation proved LA to be significantly correlated with both levels of pronunciation, with the relationship being more meaningful in the case of the perceived FL pronunciation level.